The Feasibility of a Sensate Profunda Artery Perforator Flap in Autologous Breast Reconstruction: An Anatomic Study for Clinical Application. (June 2020) - Song, Bin; Kumbla, Pallavi Archana; Boyd, Carter; de la Torre, Jorge I.; Fix, Jobe
Abstract : Background: The profunda artery perforator (PAP) flap has been demonstrated to be an effective method of autologous breast reconstruction, particularly when the abdominal donor site is contraindicated. However, there are no current reports regarding the use of a sensate PAP flap in this type of reconstruction. The objective of this study is to describe the feasibility and anatomic location of the sensory nerves supplying the PAP flap in relation to surface landmarks for use in autologous breast reconstruction. Methods: In this anatomic study, 10 cadaver lower limbs were microsurgically dissected. We investigated the posterior femoral cutaneous nerve (PFCN), which supplies sensation to the skin of the posterior thigh and distribution of the PAP flap. The midline of the posterior thigh and gluteal crease were used for surface landmarks. The diameter and length of the nerve branches were documented. Results: There were between 2 and 5 PFCN branches, with an average of 3 branches, that were found within the distribution of the PAP flap. Measurements were taken from the gluteal crease and midline to the nerve branches. The average distance caudal to the gluteal crease was 2.4 cm (0 to 7 cm). The average distance medial to the midline was 4.3 cm (0.2 to 8.1 cm). The average diameter of the nerve branches was 1.8 mm (1 to 2.5 mm). The average length of nerve branches from the flap to the fascia was 2.0 cm (1.5 to 2.4 cm). The maximum length of the nerve branches from the flap to the main trunk of the PFCN was 7.8 cm when tracing the nerve branches intramuscularly. Conclusions: The findings from this study provide an anatomic basis for the sensate PAP flap that would potentially provide an additional dimension to the use of this perforator flap in autologous breast reconstruction. These preliminary results are promising, and further physiological studies are warranted to validate the use of this sensate flap.